Title not available in English. - Levy, Maria Stella Ferreira (1991)
International immigration and fertility. From the end of the nineteenth century till approximately 1930, the International migratory current to Brazil was intense, concentrating in the State of São Paulo, due to the expansion of the cultivation of coffee. Italians formed the largest group, with significant numbers of Spaniards, Portuguese and Japanese. Due to the characteristics of a frontier region, it is believed that there was an increase in the children of the foreign women, as decribed by other authors in relation to the Southern States of the Country. The analysis of the available information about the age distribution and birthrate of foreigners as well as reasons of sex, the nuptiality permits one to conclude that the intense demographic increment in the State of São Paulo was not only due to foreign immigration, but also to an increase in the fertility of the migrant women. A process of decline in fertility would have already started around 1940, whose impact was minimized by the growing local migration (specially from the Northeast), in detriment of the International immigration.